2022
DOI: 10.1016/j.jad.2022.01.100
|View full text |Cite
|
Sign up to set email alerts
|

Generalized anxiety disorder during COVID-19 in Canada: Gender-specific association of COVID-19 misinformation exposure, precarious employment, and health behavior change

Abstract: Background Growing evidence has demonstrated the mental health sequelae of the COVID-19 pandemic. Few studies have examined how pandemic-related stressors and resilience factors of anxiety affect women and men differently in Canada. Methods Population-based data from the Canadian Perspective Survey Series (CPSS-4: July 20 to 26, 2020) were analyzed to examine the relationship between Generalized Anxiety Disorder-7 scale (GAD-7) with COVID-19 misinformation exposure, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 80 publications
0
18
0
3
Order By: Relevance
“…Employment status was a variable to investigate the pandemic's impact on labour participation (defined as those who had worked at least one hour for pay, including self-employment) in the past 7 days prior to the survey (i.e., June 7 to June 13, 2020), with a specific focus to detect precarious employment/job precarity caused by the COVID-19 pandemic [24]. Consistent with prior literature [24], the response was categorized into five groups: (1) employed and at work for at least part of the week; (2) employed but absent for the entire week due to COVID-19 (e.g., business closure, layoff, or personal circumstances including COVID-19 diagnosis); (3) employed but absent for the entire week due to other reasons not related to COVID-19 (e.g., vacation, work schedule, seasonal business, maternity or parental leave, illness other than COVID-19); (4) not employed; (5) not stated. To measure the direct disruption from the COVID-19 pandemic, respondents who had a casual job with no work available at reference week were not considered as absent from work.…”
Section: Other Potential Confoundersmentioning
confidence: 99%
See 1 more Smart Citation
“…Employment status was a variable to investigate the pandemic's impact on labour participation (defined as those who had worked at least one hour for pay, including self-employment) in the past 7 days prior to the survey (i.e., June 7 to June 13, 2020), with a specific focus to detect precarious employment/job precarity caused by the COVID-19 pandemic [24]. Consistent with prior literature [24], the response was categorized into five groups: (1) employed and at work for at least part of the week; (2) employed but absent for the entire week due to COVID-19 (e.g., business closure, layoff, or personal circumstances including COVID-19 diagnosis); (3) employed but absent for the entire week due to other reasons not related to COVID-19 (e.g., vacation, work schedule, seasonal business, maternity or parental leave, illness other than COVID-19); (4) not employed; (5) not stated. To measure the direct disruption from the COVID-19 pandemic, respondents who had a casual job with no work available at reference week were not considered as absent from work.…”
Section: Other Potential Confoundersmentioning
confidence: 99%
“…In addition, the inadequacy of culturally sensitive health care [22], the lack of interpretation services [15], limited health insurance eligibility [17] and the arbitrary 3-month wait period for insurance coverage [23] further exacerbate im/migrants' mistrust in the Canadian health care system. These pre-existing access problems, together with recently widespread misinformation around the pandemic [24] (i.e., the COVID-19 "infodemic"), could give rise to the vaccine hesitancy-one of the top 10 global health threats in 2019 as declared by the World Health Organization (WHO) [25]as well as stigma and fear accompanying COVID-19-"the greatest enemy" named by the United Nations [26].…”
Section: Introductionmentioning
confidence: 99%
“…Research has since revealed some predictors of higher compliance with public health measures during the pandemic, notably older age ( Brouard et al, 2020 ; Haischer et al, 2020 ; Solomou and Constantinidou, 2020 ) and female gender ( Clark et al, 2020 ; Galasso et al, 2020 ; Haischer et al, 2020 ; Solomou and Constantinidou, 2020 ; Nivette et al, 2021 ). Higher self-efficacy ( Clark et al, 2020 ; Hamerman et al, 2021 ; Jørgensen et al, 2021 ), higher perceived vulnerability to disease ( De Coninck et al, 2020 ; Hromatko et al, 2021 ), higher trust in science ( Hromatko et al, 2021 ; Plohl and Musil, 2021 ), prosocial personality traits ( Dinić and Bodroža, 2021 ; Nivette et al, 2021 ; Ścigała et al, 2021 ), and lower exposure to misinformation ( Roozenbeek et al, 2020 ; Simonov et al, 2020 ; Greene and Murphy, 2021 ; Lin, 2022 ) have also been linked to higher compliance with public measures. We aimed to investigate whether pandemic-related affective states also predicted compliance with public health measures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these considerations, the GAD-5 is a useful alternative in the general population that can be used in primary care settings, like the GAD-7 ( 11 , 12 , 27 31 ), and during health emergencies such as the COVID-19 pandemic. In this respect, the GAD-5 offers the practicality of web-based application in addition to the novelty of the response format used.…”
Section: Discussionmentioning
confidence: 99%